2010
DOI: 10.1177/000313481007601023
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on the Clinical Experience with AlloDerm in Breast Reconstruction and its Radiologic Appearance

Abstract: Human acellular tissue matrix (AlloDerm) use in breast reconstruction has become popular. Traditionally used for prosthesis coverage, it is also used in our practice as a filler for lumpectomy defects and a contouring device. However, no report presently exists that describes its appearance on oncologic surveillance studies. We performed a retrospective review of all charts of patients having undergone cancer-related breast reconstruction using AlloDerm as a filler at a single institution between 2005 and 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…ADMs are increasingly used as fillers in breast conserving surgery. Recent studies have reported that volume replacement with ADMs was a safe and cosmetically beneficial procedure [4] , [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ADMs are increasingly used as fillers in breast conserving surgery. Recent studies have reported that volume replacement with ADMs was a safe and cosmetically beneficial procedure [4] , [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
“…They may appear as iso-to-hypoechoic masses with a folded, sheet-like structure with posterior acoustic shadowing, and with or without color flow [7 , 8] . On MRI, an ADM shows iso-signal intensity to glandular tissue in a non fat-satured T1-weighted image, and low signal intensity in a fat-saturated T2-weighted image with none to mild dynamic contrast enhancement [4 , 8 , 9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is processed to remove antigenic epitopes from cells and provide a biologic scaffold to enhance host cell migration, cell regeneration, and angiogenesis. [1][2][3] Acellular dermal matrix was first described for use in breast reconstruction by Breuing and Warren 4 in 2005. In the same year, it was also proposed as an adjunct in neonipple reconstruction for the purposes of improving support and projection.…”
mentioning
confidence: 99%
“…Acellular dermal matrix (ADM) is an increasingly popular alloplastic cadaveric dermis used in various surgical interventions to enhance postmastectomy reconstruction. It is processed to remove antigenic epitopes from cells and provide a biologic scaffold to enhance host cell migration, cell regeneration, and angiogenesis 1–3 . Acellular dermal matrix was first described for use in breast reconstruction by Breuing and Warren 4 in 2005.…”
mentioning
confidence: 99%